2016
DOI: 10.1021/acs.jpcc.6b08611
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Electrooxidation Mechanism of Formic Acid on Pt Layers on Au Examined by Electrochemical SERS

Abstract: The electrooxidation of formic acid (FA) on Pt has received great attention because of its fundamental significance as a model reaction and its technical importance in fuel cells. Pt layers modified on Au surfaces were recently reported to exhibit enhanced electrocatalytic activity for FA oxidation; however, the mechanistic details have not been clearly elucidated. In this work, the mechanism of FA electrooxidation on Pt layers on Au surfaces was investigated via in situ electrochemical surface-enhanced Raman … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…For example, Behm and co-workers demonstrated that CO ads could replace H ads as the capping agent for Pt, and Vanpaemel and co-workers reported that ultrathin Ni films could be deposited onto TiN. The HT method has also been adapted for Pt deposition onto: Ni, star-shaped dendritic Au nanorods, and carbon fiber substrates; , Ir deposition on Au, Pt, and Ni; and for PtCoNi alloy formation . To the best of our knowledge, however, the efficacy of this method has not been tested for ML shell deposition onto nanoparticles (NPs).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Behm and co-workers demonstrated that CO ads could replace H ads as the capping agent for Pt, and Vanpaemel and co-workers reported that ultrathin Ni films could be deposited onto TiN. The HT method has also been adapted for Pt deposition onto: Ni, star-shaped dendritic Au nanorods, and carbon fiber substrates; , Ir deposition on Au, Pt, and Ni; and for PtCoNi alloy formation . To the best of our knowledge, however, the efficacy of this method has not been tested for ML shell deposition onto nanoparticles (NPs).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that Pt-based catalyst adsorbed CO easily and thus make it poisoned. 10,11 On the contrary, the direct pathway of formic acid oxidation to CO 2 is a preferred pathway on Pd catalyst, which avoids catalyst poisoning. Therefore, Pd is more promising than Pt for formic acid electrocatalytic oxidation.…”
mentioning
confidence: 99%
“…Pt NPs layered on gold surface has shown enhanced electro-catalytic activity of formic acid oxidation. [103] Likewise, Pt modified gold NPs showed high electro-catalytic activity than pure Pt NPs. [104]…”
Section: Electrochemical Oxidation Of Formic Acidmentioning
confidence: 99%